The Pied Piper of Hamelin - Illustrated by Holder, John (London Ladybird Books)
Features a Level Four tale for children who are ready to read stories with a wider vocabulary.
Include Color Illustration
Keywords: Pied Piper of Hamelin (Legendary character) -- Readers (Elementary)